GAMBARAN KESEHATAN FISIK PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Syahrizal; Wahyu Agustina (Jurnal Keperawatan Dan Kesehatan Holistik, 2025)
Chronic kidney failure is a progressive, irreversible kidney function, fluid and electrolyte imbalance causing retention of urea and other nitrogenous waste in the blood. Hemodialysis is a method of flowing blood into a dialyzer (artificial kidney tube). While physical health is a condition of the human body where every organ or part of the human body functions well, while patients with chronic kidney failure do not support. This study uses a Cross Sectional research design with a "Descriptive Survey" approach with a population of 83 people in the hemodialysis room of the Setio Husodo Kisaran Hospital. The sampling technique uses the Saturated Sampling technique with a sample size of 20 respondents. Data collection techniques by means of observation interviews, documentation, and filling out questionnaires and using yes and no categories.From the results of this study, the results obtained were the majority of male patients aged 26-35 years, a history of undergoing hemodialysis <1 year with good physical health of 74%. The conclusion is that the physical health of chronic kidney failure patients is in the good category. It is hoped that chronic kidney failure patients who have experience with hemodialysis can improve their physical health even more. The better their physical health, the less complaints will be experienced by chronic kidney failure patients.